2016
DOI: 10.3390/nu8100646
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Betaine Supplementation throughout Gestation and Lactation Modifies Hepatic Cholesterol Metabolic Genes in Weaning Piglets via AMPK/LXR-Mediated Pathway and Histone Modification

Abstract: Betaine serves as an animal and human nutrient which has been heavily investigated in glucose and lipid metabolic regulation, yet the underlying mechanisms are still elusive. In this study, feeding sows with betaine-supplemented diets during pregnancy and lactation increased cholesterol content and low-density lipoprotein receptor (LDLR) and scavenger receptor class B type I (SR-BI) gene expression, but decreasing bile acids content and cholesterol-7a-hydroxylase (CYP7a1) expression in the liver of weaning pig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 50 publications
(56 reference statements)
1
12
0
Order By: Relevance
“…The postnatal stage, especially the weaning period, is of critical importance for animal growth and for health in adult life [47,48]. Based on our data and data from other studies, maternal nutrition programming modulates liver growth and function in offspring predominantly via epigenetic regulation [33,49,50]. Intriguingly, we demonstrated that the downregulated mRNA level of IGFBP-3 in the liver was associated with protein content.…”
Section: Discussionsupporting
confidence: 70%
“…The postnatal stage, especially the weaning period, is of critical importance for animal growth and for health in adult life [47,48]. Based on our data and data from other studies, maternal nutrition programming modulates liver growth and function in offspring predominantly via epigenetic regulation [33,49,50]. Intriguingly, we demonstrated that the downregulated mRNA level of IGFBP-3 in the liver was associated with protein content.…”
Section: Discussionsupporting
confidence: 70%
“…Rats in the high-fat group showed a higher level of LDLR compared to the control group with betaine supplemented. Previous research reported that maternal dietary betaine supplementation upregulated the protein content of LDLR in rats and chickens and increased the gene expression of LDLR in piglets [26,47,48]. However, whether betaine could regulate serum LDLC levels increased by the high-fat diet via enhancing LDLR needs further research.…”
Section: Discussionmentioning
confidence: 95%
“…SREBP-1a and SREBP-1c mainly facilitated fatty acid biosynthesis, while SREBP2 is considered to be essential for cholesterol uptake through LDL receptors and de novo cholesterol biosynthesis through mevalonate pathway (Song et al 2015). As sterol sensors, LXRs are responses to cellular sterol loading, forming obligate heterodimers with retinoid X receptors (RXRs) and triggering the expression of SREBP-1c and cholesterol efflux-related genes, and then induces triglyceride accumulation through fatty acid synthase (FAS) (Cai et al 2016). Meanwhile, cholesterol is one component of serum LDL, and is transported into liver through LDL receptor, and induces the expression of CYP7A1 and cholic acid biosynthesis (Saneyasu et al 2013).…”
Section: Discussionmentioning
confidence: 99%